1999
DOI: 10.2169/internalmedicine.38.17
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thyroid Carcinoma with Multiple Hepatic Metastases: Treatment with Transcatheter Arterial Embolization and Percutaneous Ethanol Injection.

Abstract: A 54-year-old man with medullary thyroid carcinoma in the thyroid gland was unable to undergo total thyroidectomy because the tumor had invaded the mediastinum. Radiation therapy and chemotherapy were given. Seven years later, intractable diarrhea and abdominal pain appeared, and computed tomography demonstrated hypervascular tumors in the thyroid gland and in the liver. The tumors were successfully treated with percutaneous ethanol injection to a lesion in the thyroid gland and transcatheter arterial emboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…In the case of liver metastases from GEP endocrine tumors, embolization or chemoembolization has proven efficient for the control of both symptoms and tumor masses (15). Furthermore, this procedure has been reported effective in anecdotal MTC patients (16), and during the submission of this manuscript, a study on 11 patients with liver metastases from MTC reported symptomatic improvement in all patients, with transient remission or stabilization in 60% (17).…”
Section: Edullary Thyroid Carcinoma (Mtc) Arisesmentioning
confidence: 88%
“…In the case of liver metastases from GEP endocrine tumors, embolization or chemoembolization has proven efficient for the control of both symptoms and tumor masses (15). Furthermore, this procedure has been reported effective in anecdotal MTC patients (16), and during the submission of this manuscript, a study on 11 patients with liver metastases from MTC reported symptomatic improvement in all patients, with transient remission or stabilization in 60% (17).…”
Section: Edullary Thyroid Carcinoma (Mtc) Arisesmentioning
confidence: 88%
“…[22] Liver metastases are usually multiple and are usually not amenable to surgical treatment. [1123] I-131 MIBG and 90 Yttrium DOTATOC have been used for the treatment of metastatic disease. [1224]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other forms of therapy, including chemoembolization, radioembolization, radiofrequency ablation, and cryoablation, have had limited efficacies. [3a,4] Therefore, besides surgery, there are no curative treatments for NETs and their hepatic metastases. However, even surgical resection is often followed by disease recurrence, thereby emphasizing the need for the development of other forms of therapy.…”
Section: Introductionmentioning
confidence: 99%